THE EFFECT OF HANDPHONE RADIATION ON HEMATOLOGY PROFILES - Kurniasari, Septiana; Yunus, Muhammad; Madjid, Nursia; Umar, Sartika Rusdin; Amir, Asmiati; Fuadi, Nurul (Universitas Mataram, 2023)
The use of handphone is increasing, making handphone users have to focus more on the side effects of using handphone on health. Handphone is included in the category of electromagnetic waves. Exposure to electromagnetic fields can affect human health, especially the hematological profile. This type of research is observational research with a descriptive approach. Hemoglobin, erythrocyte, leukocyte and thrombocyte levels were obtained from the results of blood checks in the laboratory. The results showed that exposure to handphone radiation caused a decrease in hemoglobin levels up to 11%, an increase in erythrocyte levels up to 13%, an increase in leukocyte levels up to 14%, and an increase in thrombocyte levels up to 35%.Handphone radiation triggersoxidative stress caused by formation of ROS (Reactive Oxygen Species).